The Implementation of the Numbered Head Together Cooperative Learning Model to Improve Students' Mathematics Learning Outcomes on Linear Equation Material at SMPN 2 Sakra: Penerapan Model Pembelajaran Kooperatif Tipe Numbered Head Together Untuk Meningkatkan Hasil Belajar Matematika Siswa Pada Materi Persamaan Garis Lurus Di SMPN 2 Sakra - Zohratul Amni; Septiawan Hadi (Institute of Educational, Research, and Community Service, 2023)
This research aims to investigate the implementation of the Numbered Head Together cooperative learning model to enhance students' mathematics learning outcomes on the topic of linear equations at SMPN 2 Sakra. The research is conducted in the form of a classroom action research involving students from class VIIB as the research subjects. In this study, the cooperative approach of Numbered Head Together is used as a teaching strategy to improve students' participation, collaboration among them, and understanding of the concept of linear equations. The research is carried out in two cycles, comprising planning, implementation, observation, and reflection. Data is collected through students' learning outcome tests and classroom observations. The research findings indicate a significant improvement in students' mathematics learning outcomes after the application of the Numbered Head Together cooperative learning model. The average scores of students in the learning outcome tests increased significantly from cycle one to cycle two. Furthermore, there was also an observed improvement in students' active participation during the learning process, their interactions within groups, as well as their comprehension of the concept of linear equations. Therefore, it can be concluded that the implementation of the Numbered Head Together cooperative learning model can enhance students' mathematics learning outcomes on the topic of linear equations at SMPN 2 Sakra